The promotion of CO dissociation by molybdenum oxide overlayers on rhodium - Szenti Imre; Deák László; Kónya Zoltán (Elsevier, 2017)
Abstract A considerable promotional effect of MoOx species observed at high pressures on the catalytic activity of rhodium initiated the present UHV model study. The MoOx overlayers formed on Rh films (0.15–20.0 ML) supported by TiO2(110) substrate were characterized by AES, TPD, work function (WF) measurements and CO adsorption. On the mixed oxide support produced by depositing 1.2 ML Mo onto TiO2(110), a new recombinative CO desorption state was observed with Tp=700 K, assigned as β-CO and related to the promotional effect of MoOx species diffused onto Rh particles of 1.0 ML coverage. The development of β-CO needs 0.5–0.7 ML threshold Rh coverage, attributable to particle size effect and geometric factors governing the CO adsorption. The β-CO state with Tp=725–742 K could also be detected on Rh films covered by MoOx moiety formed by the oxidation of Mo overlayers in O2. Remarkably, recombinative CO desorption with Tp=700 K could be observed on the Rh nanoparticles covered by MoOzCy produced from pure Mo deposits by CO adsorption, too. In harmony with the promotional effect of MoOx overlayer found at high pressures, it is established that the dissociation of CO is maximal at 0.2–0.3 ML Mo coverage, attributed to the presence of active sites at the oxide-metal interface. The low desorption peak temperature (700 K) of associative CO desorption observed in the presence of MoOx and MoOzCy overlayers indicates a low activation energy for the reactions of Oa and Ca atoms, allowing high reaction rates for these intermediates. The MoOx species exerted both promotion and inhibition effects on CO adsorption at sub-monolayer coverages, but above 1 ML it completely suppressed the reactivity of rhodium layers towards CO, suggesting that its surface concentration is a critical factor.